Profile of Predictive Factors of Response to Therapy in Patients with Diffuse Large B-cell Lymphoma in dr Soetomo General Teaching Hospital Surabaya - Mochammad Dilliawan, - (Ektodermal Displazi Grubu, 2020)
Despite the use of rituximab as a substantial treatment for Diffuse Large B-Cell Lymphoma (DLBCL), the survival rate remains low due to high incidences of relapse. Several predictive factors for relapse have been investigated however, still expensive and not applicable. Lymphocytemonocyte ratio (LMR) reported as a predictor factor for treatment responses of DLBCL patients. The aims of this study to know the profile of predictor factors include age, LDH, Ann Arbor stage, extranodal involvement and lymphocyte-monocyte ratio (LMR), with the treatment response of LNH type Diffuse Large B-Cell Lymphoma (DLBCL) patients in dr. Soetomo Surabaya.A retrospective observational descriptive study of 203 subjects undergoing R-CHOP chemotherapy during 2015- 2017. Predictor variables were age, LDH, Ann Arbor stage, extranodal involvement and LMR. Elderly > 60 more unresponsive to chemotherapy 24 (46,2%) vs 28 (19%), high LDH more unresponsive 49 (94,2%) vs 3 (5, 8%). Ann Arbor stage III-IV more responsive to chemo than stage I-II, 24 (15,9%) vs 127 (84,155). In LMR< 2,6 subgroup, 84 (55,6%) subjects showed response to chemotherapy, while in LMR < 2,6 subgroup only 67 (44,4%) subgroups showed response. The conclusion of this study are subjects ≥60 years old, high LDH ≥200 U/l, early stage of disease, extranodal involvement and LMR<2.6 had a higher risk of unresponsiveness to chemotherapy.